GEOPOLYMER CONCRETE USING CERAMIC WASTE AS A SUBSTITUTE OF COARSE AGGREGATES - Fransiskus Tandi Keny; Yulin Patrisia (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2018)
This research study the influence of ceramic waste utilization as a substitute of coarse aggregate to compressive strength of geopolymer concrete. In this research, the waste of ceramic is broken down into pieces of maximum 20 mm in size and used as a substitute for coarse aggregate. The mixture consists of coarse aggregate, fine aggregate, fly ash (450 kg/m3), NaOH and Na2Sio3 (alkaline activator with ratio of Na2SiO3 to NaOH is 2: 1) and the ratio of alkaline activator to fly ash is 0.5. Percentage of ceramics aggregate to natural coarse aggregate applied in this study are 0%, 25%, 50%, 75%, and 100%. The geopolymer concrete's mix design uses the Modified Guidelines for Geopolymer Concrete Mix Design Using Approach of Indian Standard. Testing of concrete compressive strength with 20x10 cm size test specimen at the age of 14 and 28 days.The result shows that the highest compressive strength at 14 days is 18.28 MPa with 25% percentage of ceramics, while the highest compressive strength at the age of 28 days is 20.01 Mpa with 25% percentage of ceramics. The effect of ceramic use on geopolymer concrete mixture for ages 14 and 28 days shows that up to 50% ceramic usage increase concrete compressive strength compared with normal (0% ceramic) concrete, while ceramic usage above 50% to 100% reduce compressive strength of geopolymer concrete compared to normal concrete.